In Vitro Effects of Antagonistic Microorganisms on Fusarium oxysporum [Schlecht. Emend. Synd & Hans] Infecting Arachis hypogaea L. - B. Kannabiran*, P. Rajeswari and (Journal of Phytology, 2011)
In an attempt to develop biocontrol system for management of Fusarium wilt in groundnut, Trichoderma viride, Trichoderma harzianum, and Pseudomonas fluorescens were evaluated for their antagonistic activity against Fusarium oxysporum in vitro .The conidia of Fusarium oxysporum were found to be inhibited by all the three antagonistic microorganisms. Among them, highest percent inhibition of conidial germination was brought out by Trichoderma viride [89.4%] followed by Trichoderma harzianum [85.7%] and Pseudomonas fluorescens [83.15%]and inhibition of radial mycelial growth were 86.6%, 84.0%, 60.0% respectively.This inhibition is due to the volatile and non volatile metabolites and cell wall degrading enzymes produced by Trichoderma spp . Antagonistic activity of Pseudomonas spp.against Fusarium oxysporum is mainly due to the antibiotics, Fe-chelating siderophores and hydrogen cyanide.